The effect of lycopene on antioxidant status in rainbow trout (Oncorhynchus mykiss) reared under high stocking density - Şahin, Kazım; Yazlak, Hasan; Orhan, Cemal; Tuzcu, Mehmet; Akdemir, Fatih; Şahin, Nurhan (Elsevier Science Bv, 2014)
Lycopene, the major carotenoid found in tomato, exhibits health beneficial effects by virtue of its antioxidant activity. As stocking density is known as a stress factor in fish, the effects of dietary lycopene supplementation (0, 200 or 400 mg kg(-1)) on growth performance and antioxidant status in rainbow trout under normal (20 kg m(3-1)) and high (100 kg m(3-1)) stocking density were studied. Glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) and catalase (CAT) activities were evaluated, as well as lipid peroxidation measured as malondialdehyde (MDA). Nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kappa B), erythroid-derived 2-like 2 (Nrf2) and heme-oxygenase 1 (HO-1) levels were also assayed as an indicator of detoxifying/antioxidant defense mechanisms to cope with oxidative stress. Results showed that exposure to high stocking density depressed feed intake by 6.8% and body weight gain by 12.1%, increased plasma and hepatic MDA level by 88.5 and 124.3% and decreased hepatic SOD, CAT and GSH-Px activities by 22.1, 43.4 and 51.7%, respectively. In fish under crowded conditions, an expression of hepatic NF-kappa B was increased by 71.5%, being suppressed in Nrf2 and HO-1 by 40.6 and 42.7%, respectively. Lycopene supplementation increased linearly fish growth performance and antioxidant enzyme activity, and decreased linearly MDA concentration in both low and high stocking densities. NF-kappa B levels decreased hepatic Nrf2 and HO-1 levels increased linearly with lycopene supplementation at a greater extent in fish under low stocking condition. In conclusion, dietary supplementation of lycopene to fish reduces the detrimental effects of high stocking density on growth performance and modulates oxidative status via activating host defense system at cellular level. It appears that lycopene can be added up to 400 mg kg(-1) to rainbow trout diets to improve meat quality. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Lycopene; Oxidative stress; Nuclear transcription factors; Stocking density